Setaria viridis-inspired hydrogels with multilevel structures for efficient all-day fresh water harvesting. Issue 14 (22nd March 2023) - Su, Xin; Hao, Dezhao; Li, Pei; Yang, Ming; Guo, Xinglin; Ai, Xicheng; Zhao, Tong; Jiang, Lei
Abstract : Inspired by the structure of Setaria viridis, we have developed a bionic hydrogel for efficient solar desalination and fog harvesting via 3D printing technology and the ice template method. Abstract : Producing clean water through green technology solutions to ensure a sustainable water supply has attracted tremendous research attention. Solar steam generation (SSG) and fog harvesting, respectively, through solar-to-thermal conversion and humid air, are considered the most promising ways to obtain fresh water. Various natural creatures possess unique structural features that have harnessed their surface structures to collect fog and pump water underground for survival. Here we show an all-day freshwater-harvesting device of hydrogels with multilevel structures inspired by Setaria viridis . The biomimetic hydrogels with conical spines, a groove structure, and aligned vertical channels inside are developed by combining 3D printing and the ice template method. The hydrogels show superior capabilities for efficient fog capturing and photothermal evaporation. At night, the directional thorns, groove structure, and superhydrophilic surface facilitate the rapid transport of water through the super-spreading of the liquid film. During the daytime, long-range aligned vertical channels pump water to the surface of the increased evaporative area. These rich multi-structured hierarchical systems achieve evaporation rates of 3.5 kg m −2 h −1 and fog collection rates of ∼5 g cm −2 h −1, respectively. We envision that the biomimetic design strategy could be extended and used to improve the efficiency of all-day fresh water harvesting.